Correcting duplicate publications : follow up study of MEDLINE tagged duplications - Malički, Mario (Array, 2018)
Introduction: As MEDLINE indexers tag similar articles as duplicates even when journals have not addressed the duplication(s), we sought to determine the reasons behind the tagged duplications, and if the journals had undertaken or had planned to undertake any actions to address them.Materials and methods: On 16 January 2013, we extracted all tagged duplicate publications (DPs), analysed published notices, and then contacted MEDLINE and editors regarding cases unaddressed by notices. For non-respondents, we compared full text of the articles. We followed up the study for the next 5 years to see if any changes occurred.Results: We found 1011 indexed DPs, which represented 555 possible DP cases (in MEDLINE, both the original and the duplicate are assigned a DP tag). Six cases were excluded as we could not obtain their full text. Additional 190 (35%) cases were incorrectly tagged as DPs. Of 359 actual cases of DPs, 200 (54%) were due to publishers’ actions (e.g. identical publications in the same journal), and 159 (46%) due to authors’ actions (e.g. article submission to more than one journal). Of the 359 cases, 185 (52%) were addressed by notices, but only 25 (7%) retracted. Following our notifications, MEDLINE corrected 138 (73%) incorrectly tagged cases, and editors retracted 8 articles.Conclusions: Despite clear policies on how to handle DPs, just half (54%) of the DPs in MEDLINE were addressed by journals and only 9% retracted. Publishers, editors, and indexers need to develop and implement standards for better correction of duplicate published records.